Information and document flows in organizational environments - Nascimento, Natalia Marinho do; Cabero, María Manuela Moro; Valentim, Marta Lígia Pomim [UNESP] (IGI Global, 2021)
Information and document flows are essential to support all functions and activities in an organization. Information and knowledge flows in an organization are monitored; however, they are not always well managed, and members of the organization rarely perceive how and how much they contribute to their administrative processes. The purpose of this chapter is to analyze how information and document flow can be managed within an organization in a way that optimizes the access and retrieval efficiency. It is qualitative and descriptive research. The authors conclude that (a) recognition and mapping of information and document flows are fundamental for their efficient management and (b) the use of ISO records management standards such as ISO/TR 26122:2008 is the basis for formal or structured information flows. An archivist is the professional best suited to manage that flow of information, including creation, adaptation, and implementation of improvements.